Inter-relações entre a qualidade do ar externo e interno em espaços hospitalares : o complexo de doenças infecto-contagiosas Dr. Clementino Fraga em João Pessoa-Paraíba - Freire, Sheila Azevedo (2005)
This work has evaluated the quality of indoor air, from both biological and physicochemical points of view, in the Complexo de Doenças Infectocontagiosas Dr. Clementino Fraga , João Pessoa - Paraíba, using the Square Sampling technique, the air-exposing method by impactation with a linear accelerator, and a series of temperature, air humidity and speed and direction of internal and external winds data, collected in loco, and whose results, once compared with the indicators recommended by the Agência Nacional de Vigilância Sanitária ANVISA (Portuguese for Sanitary Vigilance National Agency), have shown unacceptable levels of air contamination Indoor air quality; Hospital infection; hospital architecture; natural ventilation.